2021
DOI: 10.1002/path.5663
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and research applications of multiplexed immunohistochemistry and in situ hybridization

Abstract: Over the past decade, invention and adoption of novel multiplexing technologies for tissues have made increasing impacts in basic and translational research and, to a lesser degree, clinical medicine. Platforms capable of highly multiplexed immunohistochemistry or in situ RNA measurements promise evaluation of protein or RNA targets at levels of plex and sensitivity logs above traditional methods – all with preservation of spatial context. These methods promise objective biomarker quantification, markedly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…Traditional methods in identifying immune cell types, such as chromogenic IHC and flow cytometry, suffer from limitations in multicolor staining, visualizing minimally expressed antigens or difficulty in intercellular distance and interactions in situ 22 . Here, we used mfIHC, a novel method promising immune biomarker quantification 23 , markedly increased sensitivity, and single-cell resolution, to examine the change of multiple immune cell subpopulations under the chronic cigarette smoke exposure. In the study, we found a diverse immune cell infiltration in smokers' tumor specimens and smoking characteristics related cell populations, as well as different prognosis impacts of PD-L1 expression during chronic cigarette smoke exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods in identifying immune cell types, such as chromogenic IHC and flow cytometry, suffer from limitations in multicolor staining, visualizing minimally expressed antigens or difficulty in intercellular distance and interactions in situ 22 . Here, we used mfIHC, a novel method promising immune biomarker quantification 23 , markedly increased sensitivity, and single-cell resolution, to examine the change of multiple immune cell subpopulations under the chronic cigarette smoke exposure. In the study, we found a diverse immune cell infiltration in smokers' tumor specimens and smoking characteristics related cell populations, as well as different prognosis impacts of PD-L1 expression during chronic cigarette smoke exposure.…”
Section: Discussionmentioning
confidence: 99%
“…tumor Ki67 index; PD-L1+ cells in tumor and stroma; tumor-infiltrating CD8 T-cells; proliferation and activation states of endothelium, fibroblasts, or macrophages; etc). Although we used immunoperoxidase with DAB for bright-field microscopy, the re-staining protocol can be adapted to allow fluorescent-based detection or the use of other chromogens, opening up the possibility for analysis of multiple antigens on the same section, coupled with repeated re-staining operations, as required [30][31][32][33]. Thus, by correcting for the small scanner shifts and distortions of tissue sections caused by destaining/re-staining procedures, the nuclei-based coregistration of sequential scans can also be applied to the increasingly evolving multiplexed techniques to allow comprehensive automated analysis of multiple antigens (and DNA/RNA [34]) in a single tissue section from a diagnostic sample.…”
Section: Discussionmentioning
confidence: 99%
“…The GeoMx Digital Spatial Profiler workflow is flexible, enabling analysis from selected targeted oncology and immune pathways to the whole transcriptome. This technique has the potential to support the prediction of prognosis [ 44 ], offering an unprecedented view of the composition, function and location of immune cells within the microenvironment in primary tumors and in sentinel lymph nodes [ 45 ].…”
Section: Session 6: At the Forefront Of Technologymentioning
confidence: 99%